MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK MENCARI PASANGAN PADA PELAJARAN IPS KELAS IV SD - Juara, Fitri (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2021)
The purpose of this study is to improve student learning outcomes. with the cooperative learning model of the technique of finding a partner in the fourth grade of SD Negeri 1 Lipu, South Buton Regency. This research is a qualitative research (field research) and the subject of this research is the fourth grade students of SD Negeri 1 Lipu, totaling 21 students. The object of this research is student learning outcomes with cooperative learning techniques to find a partner. The results of this study indicate that before applying cooperative learning techniques to find partners in social studies lessons, 8 (38%) were completed and 13 (61.9%) were incomplete and the class average was 63.80. However, after learning by using cooperative learning techniques to find partners in social studies lessons in cycle I and cycle II, data obtained that student learning outcomes increased. The learning outcomes of the first cycle stated that as many as 14 (66.6%) were completed and 7 (33.3%) were not completed and the average value was 70. Then the results of the second cycle test showed 18 (81.9%) were completed and 3 (14 ,2%) has not been completed and the average grade is 76. Thus, it can be concluded that cooperative learning techniques to find a partner can improve the learning outcomes of fourth grade students of SD Negeri 1 Lipu, South Buton Regency.